XMMU J181227.8–181234: a new ultracompact X-ray binary candidate. Issue 3 (17th April 2019) - Goodwin, A J; Galloway, D K; in 't Zand, J J M; Kuulkers, E; Bilous, A; Keek, L
ABSTRACT: We report the discovery of Type I (thermonuclear) X-ray bursts from the transient source XMMU J181227.8–181234 = XTE J1812–182. We found seven X-ray bursts in Rossi X-ray Timing Explorer observations during the 2008 outburst, confirming the source as a neutron star low-mass X-ray binary. Based on the measured burst fluence and the average recurrence time of 1.4^+0.9_-0.5 h, we deduce that the source is accreting almost pure helium ( X ≤ 0.1) fuel. Two bursts occurred just 18 min apart; the first short waiting time bursts observed in a source accreting hydrogen-poor fuel. Taking into consideration the effects on the burst and persistent flux due to the inferred system inclination of 30 ± 10°, we estimate the distance to be 14 ± 2 kpc, where we report the statistical uncertainty but note that there could be up to 20 per cent variation in the distance due to systematic effects discussed in the paper. The corresponding maximum accretion rate is 0.30 ± 0.05 times the Eddington limit. Based on the low hydrogen content of the accreted fuel and the short average recurrence time, we classify the source as a transient ultracompact low-mass X-ray binary.